Effect of Organizational Culture and Organizational Strategy towards Organizational Effectiveness with Knowledge Management as an Intervening Variable - Krie Elison Frinses; Rakhman Laba; Andi Reni (Hasanuddin Journal of Business Strategy, 2021)
Organizational effectiveness is the level of organizational success in an effort to achieve its goals and objectives. This study aims to analyze the direct influence of organizational culture and strategy on organizational effectiveness and indirect influence mediated by knowledge management at PT PLN (Persero) UPT Makassar. This research is a quantitative research using data collection method through questionnaires continued by data analysis method using PLS analysis. The results of this study found that first, the organizational culture and strategy have a positive and significant effect on knowledge management and organizational effectiveness. Second, knowledge management has a positive and significant effect on organizational effectiveness. The last is knowledge management can partially mediate between organizational culture and strategy on organizational effectiveness at PT. PLN (Persero) UPT in Makassar.